2015
DOI: 10.4149/bll_2015_125
|View full text |Cite
|
Sign up to set email alerts
|

The association of neutrophil to lymphocyte ratio with presence and severity of obstructive sleep apnea

Abstract: BACKGROUND: Obstructive sleep apnea (OSA) is characterized by reductions in breathing amplitude during sleep caused by an obstructed or collapsed upper airway. The neutrophil to lymphocyte ratio (NLR) has been proposed as a novel biomarker for systemic infl ammatory response. The aim of the present study was to evaluate the relationship between NLR and OSA. METHODS: The study population consisted of 195 consecutive patients with clinical suspicion of OSA. Full night polysomnography was performed for all patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
1
14
1
Order By: Relevance
“…Out of the included studies, the mean age for the samples ranged from 38.5 to 66 on OSA group, and 42.9 to 66 controls. Diagnostic methods we used for evaluating tobacco, alcohol and caffeine in the studies were questionnaire, and in other not report studies . Each study used specific AHI values for OSA definition through PSG.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the included studies, the mean age for the samples ranged from 38.5 to 66 on OSA group, and 42.9 to 66 controls. Diagnostic methods we used for evaluating tobacco, alcohol and caffeine in the studies were questionnaire, and in other not report studies . Each study used specific AHI values for OSA definition through PSG.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that the question “was the follow‐up carried out over a sufficient time period?” was considered not applicable for the included studies, since none of them proposed longitudinal results. Of the 11 studies included had moderate risk of bias, and 2 as low risk of bias . Decisions regarding individual domains within the ‘Risk of bias’ tool were observed in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Platelet activation plays a role in inflammatory process upregulation by interacting with leukocytes as well as endothelial adhesion and aggregation [21] Inflammatory markers related to the severity of the disease In our study, NLR PLR and MPV were found to be comparable between the mild and moderate OSAS patients' group and the severe patients' group. It has been reported that NLR can give an idea about the presence and severity of OSAS [22]. In a study conducted by Sünbül et al [22] 130 OSAS patients and 65 healthy subjects were compared and NLR was found significantly higher than healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that NLR can give an idea about the presence and severity of OSAS [22]. In a study conducted by Sünbül et al [22] 130 OSAS patients and 65 healthy subjects were compared and NLR was found significantly higher than healthy subjects. In addition, it was stated that AHI score and NLR values showed a significant correlation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation